Renin inhibition with aliskiren in hypertension: focus on aliskiren/hydrochlorothiazide combination therapy - Kalathil K Sureshkumar (Vascular Health and Risk Management, 2008)
Kalathil K SureshkumarDivision of Nephrology and Hypertension, Allegheny General Hospital, Pittsburgh, Pennsylvania, USAAbstract: Hypertension is a major risk factor for the development of cardiovascular and renal disease. The incidence of hypertension is increasing globally and the rate of blood pressure control remains inadequate. Renin-angiotensin-aldosterone system (RAAS) plays a crucial role in volume regulation and maintenance of blood pressure. Pathological activation of RAAS results in chronic hypertension and consequent end organ damage. Most patients with hypertension require combination therapy using agents with complimentary mechanisms of action. Hydrochlorothiazide (HCTZ) together with an agent blocking the RAAS such as an angiotensin converting enzyme (ACE) inhibitor or angiotensin receptor blocker (ARB) are widely used effective anti-hypertensive therapy. Aliskiren is an orally effective direct renin inhibitor that blocks the generation of angiotensin I from angiotensinogen, the rate limiting step of RAAS activation. Studies have shown equivalent antihypertensive efficacy of aliskiren when compared to existing medications such as HCTZ, ACE inhibitors and ARBs. Aliskiren has also been tested in combination therapies. The current review aims to look at the efficacy of aliskiren therapy in hypertension and the evidence for using aliskiren in combination with HCTZ.Keywords: hypertension, renin-angiotensin-aldosterone system, aliskiren, aliskiren-hydrochlorothiazide, combination therapy, renin inhibitors